2017
DOI: 10.1016/j.brainresbull.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Intra-vermis H4 receptor agonist impairs performance in anxiety- and fear-mediated models

Abstract: The neural histaminergic system modulates cognitive performance in various animal models. However, little is known about the effects of the H4 histaminergic receptor in the central nervous system. The purpose of this study was to investigate the effect of histaminergic H4 agonist VUF-8430 microinjection into the cerebellar vermis on the consolidation of emotional memory in mice subjected to the elevated plus maze (EPM) and inhibitory avoidance task (IAT). All experiments were performed on two consecutive days:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…On the other hand, a study by Galeotti et al (6) showed that VUF-8430 microinjected icv in mice reversed deficits in emotional memory induced by scopolamine in the IAT, but the microinjection alone did not show effects on emotional memory. In the present study, we showed that the acute administration of VUF-8430 induced a significant repression of CREB signaling expression in the cerebellar vermis that is associated with cognitive impairment, which could be related to the biochemical events associated with cognitive impairment found in our previous study (7).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…On the other hand, a study by Galeotti et al (6) showed that VUF-8430 microinjected icv in mice reversed deficits in emotional memory induced by scopolamine in the IAT, but the microinjection alone did not show effects on emotional memory. In the present study, we showed that the acute administration of VUF-8430 induced a significant repression of CREB signaling expression in the cerebellar vermis that is associated with cognitive impairment, which could be related to the biochemical events associated with cognitive impairment found in our previous study (7).…”
Section: Discussionsupporting
confidence: 74%
“…Sanna et al (8) suggested that the H4 receptor subtype did not play a prominent role in the histaminergic modulation of memory processes; however, a recent study performed in our laboratory (7) showed that intravermis microinjections of VUF-8430 induced a deficit in memory consolidation in mice subjected to the EPM and IAT tests. On the other hand, a study by Galeotti et al (6) showed that VUF-8430 microinjected icv in mice reversed deficits in emotional memory induced by scopolamine in the IAT, but the microinjection alone did not show effects on emotional memory.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations